Comparative Analysis of Credit Risk Management Practices: A Study of Domestic and Joint Venture Commercial Banks in Nepal - Bist, Roshani (Apex Journal of Business and Management, 2024)
The capital adequacy ratio, credit to deposit ratio, bank size, leverage ratio, loan loss provision, and non-performing loans were assessed for determining the relationships within domestic and joint venture commercial banks in Nepal. Using secondary data from 10 commercial banks spanning 2006/09 to 2019/20, totaling 140 observations, the study employs descriptive and regression analyses. Data sources include NRB's Banking and Financial Statistics, annual supervision reports, and selected banks' annual reports. HBL has the highest average non-performing loan (2.56%), while NIC Asia has the lowest (0.23%). SCBL exhibits the highest average capital adequacy ratio (15.92%), and SBL leads in credit to deposit ratio (86.85%). EBL tops in bank size (Rs 85,327 million), and MBL in leverage ratio (19.39%). HBL records the highest loan loss provision ratio (1.49%), with NBL at the lowest (0.32%). Descriptive statistics reveal the mean non-performing loan for domestic banks (1.12%), joint venture banks (1.22%), and overall banks (1.17%). The correlation analysis indicates negative correlations between capital adequacy ratio, bank size, credit to deposit ratio, leverage ratio, and loan loss provision with non-performing loans. Regression results underscore the significance of leverage ratio and loan loss provision in impacting non-performing loans for overall banks, while domestic banks find significance only in loan loss provision. Joint venture banks show significance in leverage ratio and loan loss provision.